Analysis of Water Quality in Abandoned Illegal Gold Mining Pit in Ketapang Regency, West Kalimantan, Indonesia - Desyana Ghafarunnisa; Flaminggo Gingga; Syarifah Aqla (Journal of Applied Sciences, Management and Engineering Technology, 2026)
Unlicensed Gold Mining (UGM), commonly carried out using open-pit methods, leaves behind excavation voids. Over time, these voids serve as catchment areas for rainwater and surface runoff. When not properly managed and repurposed after mining activities cease, such voids may pose negative environmental impacts, including the formation of acid mine drainage. Acidic water has the potential to contaminate surrounding surface and groundwater, threatening ecosystems and public health. Moreover, the presence of heavy metals in void water raises concern due to their long-term toxicity, thus requiring comprehensive studies to assess water quality conditions in abandoned unlicensed gold mine voids. The urgency of this research lies in addressing the environmental risks posed by voids left from unlicensed gold mining, particularly concerning water quality. Therefore, this study aims to analyze the water quality of such voids in accordance with national environmental quality standards. The research employed direct surveys, water sampling from voids, and laboratory analyses with test parameters based on Government Regulation No. 22 of 2021 on Environmental Protection and Management, Annex VI, including temperature, TDS, pH, CN⁻, and Hg. The results were compared to the National Water Quality Standards stipulated in the same regulation. This study is expected to demonstrate whether the water quality in mining voids falls below the permissible limits of environmental standards, indicating safety for the environment and potential utilization by surrounding communities.Keywords: Environmental quality standards; water quality; water pollution; gold mining; void)